FTIR Spectral Study on Jaundice Blood Samples Before and After Treatment - GUNASEKARAN†, S.; UTHRA*, D.; SAILATHA†, E.; ANITA†, B. (Asian Journal of Chemistry, 2024)
Spectroscopy is emerging as a potential diagnostic tool in the medical and pharmacological fields to provide information about the different chemical and morphological structures of healthy and pathological tissues. Blood being the chief circulatory medium of our body, reflects the physio-logical and pathological changes that take place in the tissues, which leads to the changes in the various plasma and cellular constituents. In the present work, FTIR spectroscopy technique is employed to study the spectral differences in the serum from healthy subjects and patients affected by jaundice, before and after they underwent treatment. Based on the differences in the spectral signatures, four intensity ratio parameters are used and their variation has been studied to understand the spectral changes. Student's t-test has been used to anlayze the set of data obtained from sera of patients pre-treatment and post-treatment.